Experiences of older adults accessing specialized health care services in rural and remote areas: a qualitative systematic review. Issue 6 (16th June 2021) - Parsons, Karen; Gaudine, Alice; Swab, Michelle
ABSTRACT: Objective: The objective of this review was to synthesize the literature on the experiences of older adults accessing specialized health care services while living in remote or rural areas. Introduction: Older persons with chronic illnesses often need specialized health care services. Those who live in remote or rural areas may have limited access to these specialized health care services, potentially leading to an increase in morbidity and mortality. Little is known about the experiences of older adults accessing specialized health care services while living in remote or rural areas. Inclusion criteria: This review considered studies of persons 65 years and older who have self-identified as living in remote or rural areas. They will have, on at least one occasion, sought access in person to specialized health care services for a chronic condition such as cardiovascular disease, renal disease, diabetes, cancer, mental illness, or a major health concern beyond the scope of a primary care clinician, such as palliative care. Methods: The search strategy aimed to find both published and unpublished studies in English from 1980 onward. An initial limited search of MEDLINE and CINAHL was undertaken in February 2017, followed by analysis of the text words contained in the title and abstract, and of the index terms used to describe the articles. This informed the development of a search strategy, which was tailored for each information source. The search was first conducted in December 2018 and rerun in November 2019. The databases searched included CINAHL, PubMed, PsycINFO, and AgeLine. The search for unpublished studies included ProQuest Dissertations and Theses, Google Scholar, and MedNar. Papers meeting the inclusion criteria were appraised by two independent reviewers for methodological quality. Data extraction was conducted according to the standardized data extraction tool from JBI. The qualitative research findings were pooled using the JBI method of meta-aggregation. Results: Three papers were included in the review yielding a total of five findings and two categories. The categories were aggregated to form one synthesized finding: Distance often results in challenges accessing health care. For almost all older adults, the long distance to drive for specialized services was a barrier, especially for those living far out in the country, and led to delayed care. Lack of health education and peer support was also viewed as an issue. For one older adult, however, the distance was not seen as an issue; rather, it was viewed as an opportunity to enjoy time with family members. Participants noted that they had access to emergency care and, therefore, believed they were not putting their lives at risk by living in a rural area. The overall ConQual score was low. Conclusion: We believe that the distance to travel to obtain specialized services, as well as living in an area without specialized services, impacted this population's experience of obtaining specialized health care as well as their health. The spectrum of findings for our synthesized finding suggests that this was the case for some people, but not all. We speculate that people who have chosen to live outside an urban area or have lived in a rural area for a prolonged period come to accept their access to health care, including the distance to travel for health care and their potential for this to impact their health. The findings also suggest the older adults have a range of experiences; for some, distance was an issue and for others, it was not an issue. Some participants found living in a rural area impacted their care while others did not.